POTENSI SENGKETA DALAM PENGADAAN FOOD TRAY IMPOR PROGRAM MAKAN BERGIZI GRATIS (MBG): TINJAUAN ARBITRASE SYARI'AH TERHADAP KEHALALAN DAN ETIKA BISNIS - Zahroh, Zahrotul Laila; Moh. Humaidi, Moh. Humaidi; Erie Hariyanto, Erie Hariyanto; Rudy Haryanto, Rudy Haryanto; Fadllan, Fadllan; Zahroh, Zahrotul (LPPM STAI Muhammadiyah Probolinggo, 2026)
The Free Nutritious Meals Program (MBG) is a strategic government policy to improve the nutritional quality of students. One important component in its implementation is the procurement of food trays as a means of food distribution. However, the procurement of imported food trays from non-Muslim countries raises potential disputes related to product halal certification, business ethics, and compliance with public procurement regulations. This study aims to identify potential disputes in the procurement of imported food trays for the MBG program and examine the relevance of sharia arbitration as a dispute resolution mechanism. This study uses a normative qualitative method with a conceptual and legislative approach, through document analysis, DSN-MUI fatwas, and academic literature related to sharia economics and public procurement. The results of the study indicate that disputes may arise due to non-compliance with halal standards, non-transparent procurement practices, and the weak integration of sharia arbitration in contracts. Sharia arbitration, through institutions such as BASYARNAS, has great potential to resolve disputes fairly, quickly, and in a manner that is oriented towards the public interest.